Mesa redonda: «De la metalexicografía a la lexicografía práctica, y viceversa» - Alonso Aldama, Javier; Gutiérrez Galindo, Marco A. (Cuadernos del Instituto Historia de la Lengua, 2010)
Participantes: Elena Redonda (Universidad del País Vasco/EHU) Blanca Urgell (Universidad del País Vasco/EHU) Javier Uría (Universidad de Zaragoza) Ramón Gutiérrez (Thesaurus Linguae Latinae, Múnich) Marta Gómez (Cilengua y Universidad de La Rioja) Ana Moure (Universidad Complutense de Madrid) Christian Schmidt (Universidad de Bonn) Marco A. Gutiérrez (moderador)